Dwikenegaraan Etnis Tionghoa di Luar Tiongkok: Suatu Analisis terhadap Perspektif Pemerintah Tiongkok - Seda, Joanessa M.J.S. (Paradigma: Jurnal Kajian Budaya, 2011)
The paper is about the historical efforts made by the Chinese Qing dynasty up to the current government to bond the Chinese overseas throughout the world to funnel their financial gain to the homeland. It shows that the policy to take advantage of the Chinese overseas to send their revenues to develop China, was adopted even during the nationalist governments. However, the analysis poses the strong reason of the tie of the Chinese overseas to the homeland, that it was not only given just for its financial support, but that it has been generated by a strong sense of cultural connectedness. On the other hand, although, culturally, the Chinese are attached to their cultural heritage, efforts to force the Chinese overseas to continually support the homeland were not that successful. In the nineteenth century, the Chinese in Indonesia during the colonial time, have been granted by the emperor, a double citizenship. But after the Mao downfall, some of the Southeast Asia countries, including Indonesia, has opposed communism in the region, thus rejected the policy. The republic of Deng finally revoked the doublecitizenship policy and as a result, encouraged promotion of teaching Chinese language overseas and sending scholars to study abroad.